Preparation and performance evaluation of bio-based cryogels for micronutrient and bioactive compound encapsulation and sustained release - Khupe, Coleman Given (Stellenbosch : Stellenbosch University, 2025)
Khupe, C. G. 2025. Preparation and performance evaluation of bio-based cryogels for micronutrient and bioactive compound encapsulation and sustained release. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/4af4ee44-f007-4723-ba02-72b3ee48caf5